Antioxidant and Antityrosinase Activity of Flemingia macrophylla and Glycine tomentella Roots. (10th September 2012) - Wang, Bor-Sen; Juang, Lih-Jeng; Yang, Jeng-Jer; Chen, Li-Ying; Tai, Huo-Mu; Huang, Ming-Hsing
Abstract : The antioxidant and antityrosinase activities of the water extract of Flemingia macrophylla root (WEFM) were investigated. The results showed that WEFM exhibited radical scavenging and reducing activities, as well as ferrous ion chelating property. In addition, WEFM also protected phospholipids against oxidation, indicating that WEFM could protect biomolecules from oxidative damage. Meanwhile, in the range of 50–100 μ g/mL, the tyrosinase inhibitory activity of WEFM increased with an increase in sample concentration and was superior to that of the water extract of Glycine tomentella root (WEGT). A high performance liquid chromatography analysis was used to determine the phenolic components, revealing that daidzin, daidzein, genistin, and genistein were present in WEFM and WEGT. Acting as an antioxidant and a tyrosinase inhibitor, these bioactive constituents could contribute to the protective effects of WEFM. Overall, the results showed that WEFM might serve as a natural antioxidant and tyrosinase inhibitor.